Three new species of Austrocarabodes (Oribatida: Carabodidae) and notes on Austrocarabodes pinnatus Mahunka, 1986, from South Africa - Hugo-Coetzee, Elizabeth A. (Zootaxa, 2011)
Three new species of the oribatid mite genus, Austrocarabodes, from South Africa are described, namely A. nortoni sp. nov., A. longisetosus sp. nov. and A. crassimarginatus sp. nov.. A supplementary description is given of A. pinnatus Mahunka, 1986. The known distribution of these species is given and a key to all South African species is presented.